1995
DOI: 10.1507/endocrj.42.467
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Epidermal Growth Factor and Its Effect on Granulosa Cell Proliferation in Rat Ovary.

Abstract: Abstract.The localization of epidermal growth factor (EGF) in the ovary and its effect on proliferation of granulosa cells were investigated in gonadotrophin-primed immature female rats. Immunoreactions with anti-rat EGF monoclonal antibody were observed sparsely in the granulosa layer and antrum of follicles, but not in the theca layer or stromal tissue. The EGF-positive cells were round or oval shaped and often larger than granulosa cells. The localization and morphological appearances of these cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Cytokines produced by immune cells such as macrophages are involved in various physiological events, such as follicular development, atresia, ovulation, and luteolysis in ovaries [33,34]. Macrophages are present in the ovaries of many animal species, but it has not been clear whether they are located in the theca layer, granulosa layer, or follicular antrum [35][36][37]. In the present study, we clearly demonstrated that macrophages are located only in theca external and internal layers of healthy follicles, and that they are not in the granulosa layer or follicular antrum.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines produced by immune cells such as macrophages are involved in various physiological events, such as follicular development, atresia, ovulation, and luteolysis in ovaries [33,34]. Macrophages are present in the ovaries of many animal species, but it has not been clear whether they are located in the theca layer, granulosa layer, or follicular antrum [35][36][37]. In the present study, we clearly demonstrated that macrophages are located only in theca external and internal layers of healthy follicles, and that they are not in the granulosa layer or follicular antrum.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports have demonstrated the appearance of macrophages within the granulosa layer and antrum of ovarian growing follicles without any signs of atresia (LoUKIDES et al, 1990;FUKUMATSU et al, 1992FUKUMATSU et al, , 1995BUKOVSKI et al, 1993BUKOVSKI et al, , 1995. It seems thus safe to suppose that macrophages enter the follicles before follicular maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding that phagocytic granulosa cells act as scavengers even without the assistance by macrophages in some mature follicles may indicate that macrophages do not play a leading role in the elimination of apoptotic granulosa cells. On the other hand, previous investigators suggested that macrophages might stimulate the growth of granulosa cells with some growth factors in a paracrine fashion (FUKUMATSU et al, 1992(FUKUMATSU et al, , 1995BUKOVSK? et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented roles for EGF in the ovarian physiology. Indeed, EGF, its receptor, and mRNA were detected in the hamster, rat, and human granulosa and theca cells [4][5][6]. EGF was also detected in human and porcine follicular fluid [7,8].…”
mentioning
confidence: 98%